Enhancing offseason yam production in Nigeria - Shiwachi, H.; Kikuno, H.; Fashola, R.; Asiedu, Robert (2008)
Yam cultivation in dry season was tested in the farmer’s field at inland valley in Niger state, Nigeria. Water yam (Dioscorea alata) variety TDa 95/00328 had the greater response to the gibberellin inhibitor prohexadione-calcium (PC). The sprouting period of PC treated tuber was 21 – 27 days at December. After tuber sprouting, the plants grew in the field during January to September. Shorter sprouting period was not observed in the harvested tuber. Demand of ware yam production during off- season for yam cultivation is high in West Africa. Although yield through this cultivation was smaller than rainy season yam cultivation. The dry season yam cultivation using the gibberellin inhibitors could be new option of intensive yam cultivation technique.